Penerapan Jaringan Internet of Things pada Smartlock Pada Rumah Pintar - Agung Wahyudi (Jurnal Jaringan Komputer dan Keamanan, 2021)
The development of network technology requires humans to perform various activities quickly and control multiple devices remotely. One implementation of this rapidly developing technology is the Internet of Things (IoT). Conventional door locking systems still have several weaknesses, particularly in terms of security and efficiency. This study aims to implement an IoT-based smart lock system in a smart home so that the door-locking and unlocking process can be performed remotely via an internet network. The system was built using a NodeMCU ESP8266 microcontroller as a connector between the local network and the internet, a solenoid as the door lock actuator, and the Telegram application as the control medium. The system development method used was the Software Development Life Cycle (SDLC). Testing was carried out through hardware function tests, Wi-Fi connection tests, and control tests via Telegram. The test results showed that the smart lock system functioned properly to open and lock doors remotely, with an average response time of 2.61 seconds for the unlock condition and 5.67 seconds for the lock condition, depending on internet network quality. The findings indicate that the application of IoT in door locking systems can improve the efficiency and security of smart homes.